2019
DOI: 10.1093/mnras/stz2386
|View full text |Cite
|
Sign up to set email alerts
|

Non-detection of fast radio bursts from six gamma-ray burst remnants with possible magnetar engines

Abstract: The analogy of the host galaxy of the repeating fast radio burst (FRB) source FRB 121102 and those of long gamma-ray bursts (GRBs) and super-luminous supernovae (SLSNe) has led to the suggestion that young magnetars born in GRBs and SLSNe could be the central engine of repeating FRBs. We test such a hypothesis by performing dedicated observations of the remnants of six GRBs with evidence of having a magnetar central engine using the Arecibo telescope and the Robert C. Byrd Green Bank Telescope (GBT). A total o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…It has been hypothesized that extreme cosmic explosions such as long GRBs, superluminous supernovae, and even short GRBs due to NS-NS mergers may give birth to extremely rapidly rotating magnetars 132 . Galactic magnetars likely did not go through these extreme channels, since their birth rate is much higher than the birth rate of those explosions 133 and since the supernova remnants of some Galactic Searches for FRBs in GRB or superluminous supernova remnants have been carried out and so far fruitless 72,73 (but see ref. 74 ).…”
Section: Box 1 Comparison Of Pulsar-like Models and Grb-like Modelsmentioning
confidence: 99%
“…It has been hypothesized that extreme cosmic explosions such as long GRBs, superluminous supernovae, and even short GRBs due to NS-NS mergers may give birth to extremely rapidly rotating magnetars 132 . Galactic magnetars likely did not go through these extreme channels, since their birth rate is much higher than the birth rate of those explosions 133 and since the supernova remnants of some Galactic Searches for FRBs in GRB or superluminous supernova remnants have been carried out and so far fruitless 72,73 (but see ref. 74 ).…”
Section: Box 1 Comparison Of Pulsar-like Models and Grb-like Modelsmentioning
confidence: 99%
“…By reversing the strategy, Madison et al (2019) searched for FRBs from the directions of nearby short GRBs testing the possible existence of a young massive NS remnant capable of making FRBs, and found nothing down to the level of the faintest repetitions from FRB 121102. Men et al (2019) carried out a similar analysis for six nearby (both long and short) GRBs with magnetar evidence and excluded a source with a burst energy distribution and rate similar to 121102.…”
Section: Introductionmentioning
confidence: 99%
“…Similar surveys have been performed recently: Law et al ( 2019) observed 10 SLSN using the Karl G. Jansky Very Large Array (VLA) for 8.5 hrs at 3 GHz, where they managed to detected the persistent radio source of PTF10hgi in their radio image searching. Men et al (2019) observed five LGRBs and one short GRB for 20 hrs using the Robert C. Byrd Green Bank Telescope (GBT) at 820 MHz and 2 GHz, and the Arecibo Radio Telescope at 1.4 GHz. Madison et al (2019) observed six short GRBs, which originate from the merger of neutron stars and could leave behind a magnetar capable of producing repeating FRBs, for 20 hrs using the GBT at 2 GHz and Arecibo at 1.4 GHz.…”
Section: Introductionmentioning
confidence: 99%